A Study of Innovation and Expression of Data Visualization Techniques in Art and Design - Yuan, Feng; Liu, Han (2024 Third International Conference on Distributed Computing and Electrical Circuits and Electronics (ICDCECE), 2024)
In the advent of the information age, it is a key in many technical fields such as computer technology, multimedia technology, software technology, intelligent technology, etc. It is the technical foundation of the information society, so its development and application are very rapid, especially to the visual communication design industry has brought a great impact. The rapid development of digital technology, especially its wide application in visual communication design, makes the visual communication design under digital technology have rich and varied means and diverse styles, and shows a strong visual impact in the dissemination of visual information, which fully demonstrates the potential of the application and development of digital technology in visual communication design. This paper discusses the innovation and expression of data visualization technology in art design. Firstly, it introduces the concepts of digital technology and visual communication art, and then unfolds the narrative of the innovation of art form. The article proves through a questionnaire that the reason for 40% of the audience's preference for digital artwork is the dynamic view of digital artwork.